Formulasi dan Evaluasi Sediaan Nasal Spray Ekstrak Ubi Ungu (Ipomea batatas) Sebagai Kandidat Antihipertensi - Khairunnisa; Meri Oktarina; Retno Widiastuti; Najma Annuria Fithri; Fiony Larasati (Journal of Pharmacy and Clinical Practice, 2026)
Purple sweet potato (Ipomoea batatas L.) is a source of anthocyanins known to have activity as an Angiotensin Converting Enzyme (ACE) inhibitor, thus having potential as an antihypertensive. This study aims to formulate and evaluate nasal spray preparations of purple sweet potato extract as candidates for intranasal drug delivery. The nasal spray preparations were formulated using 0.9% NaCl, PVP, PEG, MCC, and phosphate buffer pH 5.6. The evaluation included organoleptic tests, pH, clarity, pump-delivery, viscosity, sedimentation volume, and stability for 30 days. The results showed that all formulas were liquid, cloudy white, odorless, with a pH of 5.5–6, viscosity of 12–20 mPa·s, spray distribution of 25–30%, and sedimentation volume ≥0.8, and remained stable at room temperature and refrigerator. This study demonstrates that purple sweet potato extract nasal spray has physicochemical characteristics suitable for intranasal application, with potential for further development as an alternative natural antihypertensive therapy. Keywords: Purple sweet potato, anthocyanin, antihypertensive, nasal spray, and ACE inhibitor.